2006
DOI: 10.1002/ieam.5630020306
|View full text |Cite
|
Sign up to set email alerts
|

Sediment trend analysis of the hylebos waterway: Implications for liability allocations

Abstract: Sediment trend analysis (STA) is a technique that determines the net patterns of sediment movement and their dynamic behavior or stability. The data required are the complete particle size distributions obtained from bottom grab samples collected in a regular grid over the area of interest. Appendix 1 provides the particular details of how STA is undertaken. Because many contaminants are known to associate with the natural particles contained in sedimentary deposits, STA can provide additional weight-of-eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Sampling depth is another important factor that influences the time-scale that the derived trends represent (2001). McLaren and Beveridge (2006) support that the sediment sampling depth has no significance in the determination of sediment transport trends and hence no temporal fluctuations can be identified. On the other hand Gao and Collins (2001) and LeRoux and Rojas (2007) state that the sampling depth has to be in accordance with the physical processes scale.…”
Section: Theoretical Considerations Of Grain Size Trend Analysismentioning
confidence: 87%
See 3 more Smart Citations
“…Sampling depth is another important factor that influences the time-scale that the derived trends represent (2001). McLaren and Beveridge (2006) support that the sediment sampling depth has no significance in the determination of sediment transport trends and hence no temporal fluctuations can be identified. On the other hand Gao and Collins (2001) and LeRoux and Rojas (2007) state that the sampling depth has to be in accordance with the physical processes scale.…”
Section: Theoretical Considerations Of Grain Size Trend Analysismentioning
confidence: 87%
“…The use of bi-or multimodal sediment samples is a point of controversy regarding the determination of the correct grain size trends because of their abundance in the natural environment. McLaren and Beveridge (2006) argued that the use of multimodal sediment samples is not introducing any error in the resultant trends; on the other hand, Gao and Collins (1994a), LeRoux and Rojas, (2007) suggest that the use of such sediments is introducing errors in the determination of the transport direction. A detailed analysis on the impact of bimodal sediment on grain size trends (Flemming, 2007) showed that the use of such sediment samples produce results which are unrelated to the transport processes and sample decomposition into individual populations must be undertaken to such distributions.…”
Section: Theoretical Considerations Of Grain Size Trend Analysismentioning
confidence: 96%
See 2 more Smart Citations
“…Critical to such decisions is an assessment of the likelihood for recontamination after sediment removal, a requirement that demands (i) an understanding of the physical processes that are likely affecting sediment transport, (ii) how those processes relate to the actual patterns of net sediment transport, and (iii) an identification of existing sources of contaminated sediments and their probable transport behavior. The objective of this paper is to assess and discuss each of these criteria utilizing sediment trend analysis (STA), a method that determines sediment transport pathways and dynamic behavior on the basis of the relative changes of grain-size distributions taken from the river bottom (MCLAREN AND BEVERIDGE, 2006). The results presented are from two STA Figure 1.…”
Section: Introductionmentioning
confidence: 99%